Answer:
x=2 and x=-2
Step-by-step explanation:
Original Equation:
[tex]x^2-6x=-6x+4\\[/tex]
Add 6x to both sides
[tex]x^2=4[/tex]
Subtract 4 from both sides
[tex]x^2-4=0[/tex]
Use difference of squares: [tex]a^2-b^2=(a-b)(a+b)[/tex]
[tex](x-2)(x+2)=0[/tex]
Since the factors are being multiplied by each other, if one of the factors is equal to zero, then the entire thing becomes zero, since 0 * anything = 0
So to find the values of x that satisfy this equation, set each factor equal to zero
[tex]x-2=0[/tex]
Add 2 to both sides
[tex]x=2[/tex]
[tex]x+2=0[/tex]
subtract 2 from both sides
[tex]x=-2[/tex]
We have both values that satisfy this equation, x=2 and x=-2